Learning Strategies for Islamic Religious Education to Prevent Radicalism at Tertiary Level - Moch Yasyakur; M Hidayat Ginanjar; Sarifudin Sarifudin; Agus Mailana (STAI Hubbulwathan Duri, 2023)
The emergence of radicalism in society, including on campuses, can also be associated with a universal lack of understanding and a deepening of religion. The purpose of this study was to identify and analyze Islamic education learning strategies in order to prevent radicalization among students. Islamic Religious Education (PAI) learning is the main factor that can improve a person's mindset, including students. As a result, students must be supported through effective and optimal learning strategies. Qualitative research methods are used in this research. The subjects of this study were all relevant informants and participants in the learning process at a university in Bandung, namely the coordinators of PAI lecturers, PAI lecturers, and students. Data collection methods include observation, interviews, and document studies. Data analysis uses triangulation techniques. The PAI learning strategy has been implemented effectively and adequately in an effort to prevent radicalism among students by carrying out several stages, including; planning in learning based on setting goals to be achieved in PAI learning which refers to a curriculum that is integrated with various scientific fields, using personal methods/approaches and social interactions between educators and students in the learning process, planning in learning based on setting goals to be achieved in PAI high level of understanding is one of the four indicators of program success.